1999
DOI: 10.1002/j.2161-0045.1999.tb00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Differences in College Students' Career Decision Making on the Basis of Disability Status

Abstract: and career decision-making attributional style (D. A. Luzzo & A. Jenkins-Smith, 1998). Students with disabilities reported significantly lower levels of career decision-making self-efficacy and exhibited more of a pessimistic attributional style for career decision making than did their peers without disabilities. Results are discussed in the context of developing effective career counseling interventions for college students with disabilities.Relatively little is known about the career decision-making process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 42 publications
1
45
1
3
Order By: Relevance
“…Specifically, college students with learning disabilities obtained a higher mean score when compared to the normative group on the EC scale. This is consistent with research by Luzzo, Hitchings, Retish, and Shoemaker (1999) and Luzzo and Jenkins-Smith (1998) who reported that in terms of attributional style for career decision making, students with disabilities believed external factors were responsible for career-related outcomes in their lives.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, college students with learning disabilities obtained a higher mean score when compared to the normative group on the EC scale. This is consistent with research by Luzzo, Hitchings, Retish, and Shoemaker (1999) and Luzzo and Jenkins-Smith (1998) who reported that in terms of attributional style for career decision making, students with disabilities believed external factors were responsible for career-related outcomes in their lives.…”
Section: Discussionsupporting
confidence: 92%
“…The experiences and personal perspectives of students with disabilities were not reflected in the data obtained in our initial studies and the studies by others (Hitchings et al, 1998;Luzzo et al, 1999). In our approach, we chose to treat each interview as a case study and then combined the students' verbatim accounts to help answer the questions we posed.…”
Section: Methodsmentioning
confidence: 97%
“…Učenici sa LIO imaju nekonzistentan izbor zanimanja (p=0,023) jer ne uspevaju da shvate da li su njihove lične karakteristike, sposobnosti i veštine u skladu sa izabranim zanimanjem (Jagger, Neukrug & McAuliffe, 1992), manje su informisani o zanimanjima od učenika TR (p=0,014), imaju manje iskustva u donošenju odluke (p=0,043), manje su upoznati kako se odvija obuka za zanimanje koje ih interesuje (p=0,001) i treba im znatno više podrške u izboru zanimanja od učenika TR (p=0,012). Aktivnosti istraživanja i izbora zanimanja često su ograničene za osobe sa LIO u osnovnoj školi, jer se dosta vremena utroši na akademsku remedijaciju umesto na pripreme za izbor zanimanja (profesionalna orijentacija ili usmeravanje) i profesionalno informisanje (Luzzo, Hitchings, Retish & Shoemaker, 1999). Kao rezultat toga, oni nisu svesni koja sve zanimanja postoje, šta znači pojam karijera (zanimanje, radno mesto, obuka), nisu razvili veštinu donošenja profesionalnih odluka i sposobnost rešavanja problema (Hitchings et al, 2001;Stang et al, 2009).…”
Section: Diskusijaunclassified